Three new endemic species of Muellera (Fabaceae, Papilionoideae) from Brazil - Da Silva, Marcos José; de Azevedo Tozzi, Ana Maria Goulart (Phytotaxa, 2011)
Based on studies of herbarium collections, and fieldwork in Brazil for a taxonomic revision of the genus Muellera, were discovered three new species which are described and illustrated here: M. fernandesii, M. leptobotrys and M. nitens. In addition, aspects about the morphology and the geographical distribution of these species, as well as their affinities are discussed.